Ansiedade, depressão e estresse em acompanhantes de crianças internadas com Covid-19 - Lima, Larissa Rodrigues de Freitas (2023)
In the context of the pandemic, Brazil ranked third among countries with the highest number of Covid-19 cases. The population aged 0-19 represented 8% of the cases. Hospitalization was necessary in some situations, causing fear, insecurity, and discomfort for both the child and the caregiver. This research aims to identify the levels of anxiety, depression, and stress experienced by caregivers during the hospitalization of children with Covid-19. It is a retrospective study conducted at a reference Children's Hospital in the state of Ceará. The study population consisted of 15 caregivers of children diagnosed with Covid-19 who were hospitalized during their treatment. Data collection occurred in two stages: First, participant identification through epidemiological records and complete medical record evaluation to gather the child's clinical profile and confirmation of a positive Covid-19 test. Second, telephone contact with the caregivers to explain the research and obtain their consent through the acceptance of the informed consent form, which was sent in the form of a Google form. After consent was obtained, the interview was conducted, and the caregivers completed the questionnaire. For analysis, the data were tabulated in Microsoft Excel and analyzed using the R Interface for Multidimensional Text and Questionnaire Analysis software. The study complied with Resolution No. 466/12 of the National Health Council and was submitted for approval to the Research Ethics Committee of the Federal University of Ceará and the Albert Sabin Children's Hospital, receiving approval. Regarding the children's clinical profile, they had a median age of 6 years and an average hospital stay of 7 days. Furthermore, most of them did not exhibit respiratory symptoms, require endotracheal intubation, ICU admission, or oxygen use, indicating that the majority had mild cases. Most caregivers had normal levels of stress, depression, and anxiety, with a strong positive correlation between depression and anxiety, and an association between stress levels and the mother as the caregiver. The descriptions of the caregivers' statements revealed feelings about the child's hospitalization, changes in family dynamics caused by the hospitalization, and the caregivers' positive perception of the healthcare teams. This study has implications for the professional practice of the hospital healthcare team by highlighting the need for special attention to the difficulties faced by caregivers, as they play a role in the caregiving process.